1991
DOI: 10.1093/jn/121.10.1656
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Balance and Stage of Lactation Affect Responses of Insulin, Insulin-Like Growth Factors I and II, and Insulin-Like Growth Factor-Binding Protein 2 to Somatotropin Administration in Dairy Cows

Abstract: Six Holstein cows were used in a complete block design to examine effects of period of lactation and somatotropin (bST) administration on concentrations of insulin, insulin-like growth factors (IGF-I, IGF-II), and IGF-binding protein 2 (IGFBP-2). During late lactation, the dry period and the subsequent early lactation, cows received injections of NaHCO3 buffer for 5 d and bST for 7 d. Cows were in positive energy and protein balances during late lactation and the dry period and in slight negative balances duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
103
2
5

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 26 publications
17
103
2
5
Order By: Relevance
“…(4,7,28,38,39). Our observation that low ering serum ST increased IGFBP-2 and decreased IGFBP-3 is consistent with observations that exogenous ST increased IGFBP-3 (28) and decreased IGFBP-2 in dairy cows (28,39). These data provide evidence that feed restriction in ruminants elevates ST through a mechanism involving an increase in frequency of ST release.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(4,7,28,38,39). Our observation that low ering serum ST increased IGFBP-2 and decreased IGFBP-3 is consistent with observations that exogenous ST increased IGFBP-3 (28) and decreased IGFBP-2 in dairy cows (28,39). These data provide evidence that feed restriction in ruminants elevates ST through a mechanism involving an increase in frequency of ST release.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to reports in humans (4,9) and pigs (7), we failed to observe an effect of acute feed restriction on IGFBP in ruminants. Other reports have failed to show a clear effect of feed restriction on IGFBP in ruminants (5); however, Vincini (39) reported that IGFBP-2 was higher during early lactation when cows were in negative energy balance. Gallaher (10) found that fasting castrate sheep decreased IGFBP-3 and increased IGFBP-2; however, fast ing in pregnant ewes was associated with a slight decrease in IGFBP-3, but no change in IGFBP-2.…”
Section: Discussionmentioning
confidence: 95%
“…This is related to the parallel increase in milk yield and milk protein yield (Lemosquet et al, 2004). Low circulating concentrations of IGF-1 in early lactation have been associated with negative energy balance (Spicer et al, 1990;Vicini et al, 1991) and with negative protein balance when energy balance is not already limiting (Ronge et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, IGF-I expression is no longer capable of increase in response to the secretion of GH by the pituitary (Vicini et al, 1991). This happens -E-mail: augusto.schneider@live.com because insulin concentration is reduced, and so is GHR expression in the liver (Butler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%